Pure ultrasonic communication in an endemic Bornean frog. - Victoria S Arch; T Ulmar Grafe; Marcos Gridi-Papp; Peter M Narins (PLoS ONE)
Huia cavitympanum, an endemic Bornean frog, is the first amphibian species known to emit exclusively ultrasonic (i.e., >20 kHz) vocal signals. To test the hypothesis that these frogs use purely ultrasonic vocalizations for intraspecific communication, we performed playback experiments with male frogs in their natural calling sites. We found that the frogs respond with increased calling to broadcasts of conspecific calls containing only ultrasound. The field study was complemented by electrophysiological recordings from the auditory midbrain and by laser Doppler vibrometer measurements of the tympanic membrane's response to acoustic stimulation. These measurements revealed that the frog's auditory system is broadly tuned over high frequencies, with peak sensitivity occurring within the ultrasonic frequency range. Our results demonstrate that H. cavitympanum is the first non-mammalian vertebrate described to communicate with purely ultrasonic acoustic signals. These data suggest that further examination of the similarities and differences in the high-frequency/ultrasonic communication systems of H. cavitympanum and Odorrana tormota, an unrelated frog species that produces and detects ultrasound but does not emit exclusively ultrasonic calls, will afford new insights into the mechanisms underlying vertebrate high-frequency communication.